"Don't you want the dream?": Psycho-social determinants of car share adoption. (April 2021) - Jain, Taru; Rose, Geoffrey; Johnson, Marilyn
Highlights: Key motivators of car share adoption are cost savings, environment, convenience. Normative beliefs around car ownership discourage car share adoption. People with young children perceived car share as difficult to use. Car share adoption is not a binary decision, but a multistage process. Psycho-social determinants vary for P2P and fleet-based systems. Abstract: The benefits of car share, in terms of reduced car ownership and sustainable transport use have been widely recognised. Knowledge of motivators and barriers of car share adoption is crucial to inform policy, and yet this aspect has received little attention so far. This paper aims to comprehensively explore the range of psycho-social factors which determine the adoption of car share. In this study, two theoretical approaches were used to explore psycho-social determinants of car share adoption. First, the Theory of Planned Behaviour is used as a theoretical lens to identify the role of attitudes, subjective norms and perceived behavioural control in car share adoption. Second, the Theory of Innovation Diffusion is used to examine the process of adoption of car share and the barriers at different stages. While the former considers the determinants of the binary decision of becoming a car share, the latter unpacks the process of car share adoption. This qualitative study draws on data from five focus groups and 18 semi-structured interviews, conducted in Melbourne, Australia, with station-based car share member, ex-members and non-members. Insights confirmed that while cost, convenience and environmental concerns are important motivators, others factors also encourage car share use including sharing with the community, reducing/avoiding hassles related to car ownership (e.g. maintenance, parking) and, a desire to own fewer material possessions. Normative beliefs about car ownership, perceived difficulties in using car share (e.g. with children) and the planning and effort required to book and use car share were identified as some of the barriers. Barriers related to car share use varied depending on the stage of car share adoption. Initial barriers related to a lack of knowledge and normative beliefs about car ownership. The study also highlighted how motivators and barriers might vary for peer-to-peer and fleet-based car share. Insights from this study will be useful for car share operators and policymakers to address the practical and social barriers to car share adoption.